Enhancement of waste heat collection using phase change materials - Low, Zheng Hua (2017)
Phase Change Materials (PCMs) are able to store a large amount of heat due to their high latent heat storage capability hence becoming an integral part of many waste heat collection systems. However, the use of PCMs is limited by its low heat transfer rate attributed to its low thermal conductivity. This paper presents both experimental and numerical investigation of a newly designed Thermal Energy Storage (TES) system using an organic compound, paraffin wax (RUBITHERM RT42) coupled with a few innovative methods to enhance the heat transfer rate using extended surfaces. A reasonable match between one Experimental and Numerical Simulation Results was drawn hence validating the simulation settings as well as the results of subsequent simulation for various fin designs and arrangements. Simulations using the exact same parameters with exception of geometry were executed to investigate the enhancement effect of said fins. The amount of time to achieve complete melt of PCM was used to determine the level of enhancement. From the numerical simulations, an enhancement of 8.33% in the time to achieve complete melt was seen when parallel fins were used in place of the original no fin set-up. Enhancement of 16.67% and 12.50% was noted when using tilted fins of 15o and 30o respectively. The highest enhancement came from the variable length fin with enhancement of up to 21.42%. The experiment result shows a slight enhancement when the incline angle of fin changes from 0 to 15, which accords with the numerical predictions. Melting front evolution at various time-steps were analyzed through image processing. Different melting front patterns were observed under different inclined fins. In all cases, the effect of Natural Convection played a crucial role in enhancing the heat transfer and the various fins effect on Natural Convection was briefly discussed in the paper.